Loss of Rituals, Boundaries, and Relationship: Patient Experiences of Transition to Telepsychotherapy Following the Onset of COVID-19 Pandemic - Werbart, Andrzej; Byléhn, Linda; Jansson, Tuva Maja; Philips, Björn (Frontiers in Psychology, 2022)
Telepsychotherapy is an increasingly common way of conducting psychotherapy. Previous research has shown that patients usually have positive experiences of online therapy, however with large individual differences. The aim of this study was to explore patients’ experiences of transition from in-person psychotherapy sessions to telepsychotherapy during the COVID-19 pandemic, as well as variation in the experiences with regard to the patients’ personality orientation. Seven psychotherapy patients in Sweden were interviewed and the transcripts were analyzed using thematic analysis. Additionally, the participants were asked to rate their dissatisfaction/satisfaction with the transition, how hindering/helpful the transition was, and how unsafe/safe they felt after the transition in comparison to before. Personality orientation on relatedness or self-definition was assessed applying a self-assessment instrument (Prototype Matching of Anaclitic-Introjective Personality Configuration; PMAI). The participants experienced telepsychotherapy as qualitatively different from in-person psychotherapy. They reported several essential losses: the rituals surrounding therapy sessions were lost, including the transitional time and space between their every-day life and the therapy sessions, less therapeutic work was done, the therapists could lose their therapeutic stance, the sense of rapport was impaired, and the patients felt less open and emotionally available. On the other hand, some patients could feel freer online. As six of the participants had an anaclitic personality orientation, the present study could especially contribute to the understanding of how patients with strong affiliative needs and fear of abandonment experience the transition to meeting their therapists via communication technology. The participants’ self-ratings showed that they were only marginally dissatisfied with the transition and experienced the transition as slightly hindering, whereas they felt rather safe after the transition, indicating low concordance between qualitative and quantitative evaluations. New studies are needed to explore the introjective patients’ experiences of the transition. An essential topic is also to collect evidence and to test how the impaired sense of rapport when using communication technology can be remedied by adequate, patient-tailored interventions, a topic that has to be included in psychotherapy education and training.